Dose Analysis of Boron Neutron Capture Therapy (BNCT) in Brain Cancer Based on Cyclotron Using PHITS Application Simulation - Muhammad Ghozali; Heni Sumarti (Journal of Holistic Medical Technologies (JHMT), 2025)
One of the cancers is brain cancer, the most dangerous of which is Glioblastoma Multiforme (GBM). The research conducted aims to determine the effect of boron concentration on the boron dose rate, irradiation time and absorbed dose. Current cancer treatment still provides deterministic effects (tissue reactions) of radiation to patients and long therapy times. Therefore, researchers conducted research on Boron Neutron Capture Therapy (BNCT) in the treatment of cancer patients that is more selective in destroying cancer cells and is safe because it does not damage healthy tissues around it and the therapy requires a short time. The type of research conducted is quantitative experimental research. The research method with simulation uses the Particle and Heavy Ions Transport code System (PHITS) application on therapy process of Boron Neutron Capture Therapy (BNCT) for brain cancer patients type of Glioma grade 4 called Glioblastoma Multiforme. Patient modeling is based on the Oak Ridge National Laboratory-Medical Internal Radiation Dose (ORNL-MIRD) phantom in adult men who have a brain cancer diameter of 4 cm at a depth of 7 cm with a neutron source from a 30 MeV Cyclotron. The boron concentration used has 3 variations, as follows 20 μg/g, 40 μg/g and 60 μg/g of cancer tissue. Based on the results of the study at a boron concentration of 60 μg/g in the Gross Total Volume (GTV) organ or the center of cancer cells with a dose rate value of 11,160 x 10-2 Gy/s, thus accelerating the irradiation time within a period of 4 minutes 48 seconds and the absorbed dose increases by 30 Gy. Thus, it can be concluded that the higher the boron concentration, the faster the boron dose rate value, the greater the absorbed dose and the faster the irradiation time when carrying out brain cancer therapy.